Ground penetrating radar wave attenuation models for estimation of moisture and chloride content in concrete slab. (1st March 2016) - Senin, S.F.; Hamid, R.
Highlights: GPR wave attenuation is measured on a concrete slab saturated with water and chloride. The moisture content (MC) shows a strong linear correlation with the wave attenuation. The chloride content (CC) attenuates radar waves at a higher rate than the MC. Two models to estimate MC and CC in concrete slab are proposed. The extent of these corrosion agents are useful in condition rating decisions. Abstract: The detection of moisture and chloride ingress through concrete cover is important for estimating the extent of corrosion in reinforced concrete (RC) components. The concentrations of the substances are monitored by observing the ground penetrating radar (GPR) amplitude attenuation in water and chloride saturated concrete slab samples. The amplitude attenuation significantly correlates with the amount of both substances. Two multiple nonlinear regression models were developed. The proposed models demonstrate a strong correlation with the radar amplitude attenuation data as both substances are varied in the concrete cover. The developed models can be employed to estimate the moisture and free chloride content in – concrete cover for improved quantification of corrosion level.